Pemberdayaan Masyarakat Melalui Pelestarian Kesenian Kuda Lumping - Nur Ikhfani Dwi Rizky Putri; Adang Danial; Ahmad Hamdan (Pusat Riset dan Inovasi Nasional, 2023)
The high poverty rate as well as the unemployment rate and the lack of awareness of the importance of empowerment programs in Bangunreja Village cause people to be unable to meet their needs. The Bangunreja Village Government created an empowerment program with the aim of bringing change and improving family welfare, namely the empowerment program through the preservation of the art of kuda lumping. The purpose of this study is to determine the process and results of community empowerment through the preservation of lumping horse. This research is a qualitative research using descriptive method. Data collection techniques use observation, interviews, and documentation. The analysis techniques used are data reduction, data display, and conclusions. The results showed that community empowerment through the preservation of lumping horse art was able to provide benefits to the community, namely by increasing income and the community understood the importance of the empowerment program. Increased knowledge in the community. The empowerment activities carried out include counseling and training. With the right support, this art can improve community welfare, cultural diversity, and a sense of togetherness in the community and be able to maintain a valuable cultural heritage. The conclusion of the research is that the people of Bangunreja Village are aware of the importance of community empowerment programs, the community is able to take responsibility for themselves, and the increase of the community's cultural heritage